When do elite cyclists go the extra mile? Team identification mediates the relationship between perceived leadership qualities of the captain and social laboring - de Cuyper, B.; Boen, F.; van Beirendonck, C.; Vanbeselaere, N.; Fransen, K. (International Journal of Sport Psychology, 2016)
In order for a sports team to function optimally, it is essential to avoid motivational losses due to working in a group, also known as social loafing. Ideally, team members can even show an increase in individual effort because of working in a group, which is labeled social laboring. The present study investigated the impact of the leadership qualities of the team captain on social laboring in an elite cycling context. In addition, we examined the underlying process of this effect by focusing on team identification as mediator of the relationship between transformational leadership and social laboring. Participants were 55 male cyclists at the highest competitive level of professional cycling. Structural Equation Modeling demonstrated that the more the captain was perceived as leading by example, the more teammates reported social laboring. This positive relationship was fully mediated by team identification. This finding supports the Social Identity Approach of Leadership, which proposes that social identification is the explanatory process through which contemporary leaders deliver their outcomes.